Fluorescence in situ hybridization analysis of hindgut bacteria associated with the development of equine laminitis - Gabriel J. Milinovich; Darren J. Trott; Paul C. Burrell; Emma L. Croser; Rafat A. M. Al Jassim; John M. Morton; Andrew W. van Eps; Christopher C. Pollitt (Environmental Microbiology, 2008)

Fluorescence in situ hybridization analysis of hindgut bacteria associated with the development of equine laminitis - Gabriel J. Milinovich; Darren J. Trott; Paul C. Burrell; Emma L. Croser; Rafat A. M. Al Jassim; John M. Morton; Andrew W. Van Eps; Christopher C. Pollitt (Environmental Microbiology, 2007)
Summary Carbohydrate‐induced laminitis in horses is characterized by marked changes in the composition of the hindgut microbiota, from a predominantly Gram‐negative population to one dominated by Gram‐positive bacteria. The objective of this study was to monitor changes in the relative abundance of selected hindgut bacteria that have previously been implicated in the pathophysiology of equine laminitis using fluorescence in situ hybridization (FISH). Caecal cannulae were surgically implanted in five Standardbred horses and laminitis induced by oral administration of a bolus dose of oligofructose. Caecal fluid and faecal specimens were collected over a 48 h period at 2 to 4 h intervals post‐oligofructose administration and subjected to FISH using probes specific for nine bacterial groups to determine changes in their relative abundance compared with total bacteria hybridizing to the generic EUBMIX probe. Additionally, hoof biopsies were taken over the course of the experiment at 6 h intervals and evaluated for histopathological changes consistent with laminitis, allowing changes in hindgut microbiota to be correlated with the onset of lesions in the foot. Of the microorganisms specifically targeted, streptococci of the Streptococcus bovis / equinus complex were the only bacteria that consistently proliferated in both caecal fluid and faeces immediately before the onset of histological signs of laminitis. Furthermore, lactobacilli, Enterobacteriaceae , Allisonella histaminiformans , enterococci, Bacteroides fragilis , Mitsuokella jalaludinii and Clostridium difficile did not establish significant populations in the hindgut before the onset of equine laminitis.

Localisation of gelatinase activity in epidermal hoof lamellae by in situ zymography - B. A. Mungall; Rita Collins; Christopher C. Pollitt (Histochemistry and Cell Biology, 1998)